Concentration effect relationship of CYP3A inhibition by ritonavir in humans - Eichbaum, Christine; Cortese, Marianna; Blank, Antje; Burhenne, Jürgen; Mikus, Gerd (European journal of clinical pharmacology, 2013)
To investigate the dose and concentration dependency of CYP3A inhibition by ritonavir using the established limited sampling strategy with midazolam for CYP3A activity.
Gesehen am 08.01.2021